The big cat nap [large type] : the 20th anniversary Mrs. Murphy mystery - Brown, Rita Mae (Brown, Rita Mae. Mrs. Murphy mystery., 2012)
"When a series of inexplicable car accidents are attributed to driver error, Harry Harristeen knows that something is amiss. Together with her intrepid team of feline, canine, and equine helpers, she begins to investigate."-